The Functional Orlicz Brunn-Minkowski Inequality for q-Capacity. (8th October 2020) - Wang, Wei; Li, Juan; He, Rigao; Liu, Lijuan
Abstract : In this paper, we establish functional forms of the Orlicz Brunn-Minkowski inequality and the Orlicz-Minkowski inequality for the electrostatic q -capacity, which generalize previous results by Zou and Xiong. We also show that these two inequalities are equivalent.